68Ga/64Cu PSMA Bio-Distribution in Prostate Cancer Patients: Potential Pitfalls for Different Tracers - Calabria, Ferdinando; Pichler, Robert; Leporace, Mario; Wolfsgruber, Johannes; Coscarelli, Pierluigi; Dunzinger, Andreas; Schillaci, Orazio; Cascini, Giuseppe L.; Bagnato, Antonio (Current Radiopharmaceuticals, 2019)
Background: 68Ga-PSMA is a widely useful PET/CT tracer for prostate cancer imaging. Being a transmembrane protein acting as a glutamate carboxypeptidase enzyme, PSMA is highly expressed in prostate cancer cells. PSMA can also be labeled with 64Cu, offering a longer half-life and different resolution imaging. Several studies documented bio-distribution and pitfalls of 68Ga-PSMA as well as of 64Cu- PSMA. No data are reported on differences between these two variants of PSMA. Our aim was to evaluate physiological distribution of these two tracers and to analyze false positive cases. Methods: We examined tracer bio-distribution in prostate cancer patients with negative 68Ga-PSMA PET/CT (n=20) and negative 64Ga-PSMA PET/CT (n=10). A diagnostic pitfall for each tracer was documented. Result: Bio-distribution of both tracers was similar, with some differences due to renal excretion of 68Ga- PSMA and biliary excretion of 64Cu-PSMA. 68Ga-PSMA uptake was observed in sarcoidosis while 64Cu- PSMA uptake was recorded in pneumonitis. Discussion: Both tracers may present similar bio-distribution in the human body, with similar uptake in exocrine glands and high intestinal uptake. Similarly to other tracers, false positive cases cannot be excluded in clinical practice. Conclusion: The knowledge of difference in bio-distribution between two tracers may help in interpretation of PET data. Diagnostic pitfalls can be documented, due to the possibility of PSMA uptake in inflammation. Our results are preliminary to future studies comparing diagnostic accuracies of 68Ga-PSMA and 64Cu-PSMA.
Keywords: prostate cancer